The Role of Amanah and Tabligh in Strengthening Islamic Banking Relationships - Mutia Tsalitsa Alawia; Wiwik Mukholafatul Farida; Shinta Laura Dewani (CV Edujavare Publishing, 2026)
This study aims to analyze agency problems in murabahah and mudharabah contracts and to identify strategies to reduce these issues in Islamic banking practices. The research employs a qualitative approach using a library research method by reviewing various sources, including academic journals, books, and other relevant literature published between 2021 and 2025. The findings indicate that agency problems in Islamic banking primarily arise from information asymmetry and moral hazard between the bank as the principal and the customer as the agent. These issues are more prevalent in mudharabah contracts compared to murabahah, due to the high dependence on the honesty and transparency of customers in reporting business performance. In contrast, murabahah contracts tend to have lower agency risks because of their simpler and more transparent transaction structure. Furthermore, this study finds that the implementation of tabligh (transparency) and amanah (trustworthiness) principles serves as an effective solution in reducing information asymmetry and moral hazard. Therefore, strengthening Islamic ethical values along with improving monitoring systems and transparency mechanisms is essential to mitigate agency problems and to optimize the implementation of profit-and-loss sharing contracts in Islamic banking.